2020
DOI: 10.1002/lno.11604
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution distribution pattern of surface water nitrous oxide along a cruise track from the Okhotsk Sea to the western Arctic Ocean

Abstract: Nitrous oxide in the surface water was measured using an automatic underway system, along with measurements of surface water pCO 2 , dissolved oxygen, salinity, temperature, and sea ice coverage, along a cruise track through the Bering Sea and Chukchi Sea to the Canadian Basin during the 7 th Chinese National Arctic Research Expedition. The results show that, overall, the regions along the cruise track are net sources of N 2 O to the atmosphere. Several N 2 O oversaturation maxima were observed along the cruis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Oceanic N 2 O production and consumption rates are controlled by a wide range of biogeochemical processes, for example, nitrification and denitrification (Bange et al., 2010; Codispoti, 2010) and are likely to be impacted by ongoing Arctic change. Some studies have reported that significant N 2 O supersaturation can occur, but is not ubiquitous, in the Bering and Chukchi Seas (Hirota et al., 2009; Toyoda et al., 2021; Zhan et al., 2021). Fewer published N 2 O data exist in other North American Arctic Ocean regions, including the Northwest Passage and Baffin Bay (Kitidis et al., 2010; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oceanic N 2 O production and consumption rates are controlled by a wide range of biogeochemical processes, for example, nitrification and denitrification (Bange et al., 2010; Codispoti, 2010) and are likely to be impacted by ongoing Arctic change. Some studies have reported that significant N 2 O supersaturation can occur, but is not ubiquitous, in the Bering and Chukchi Seas (Hirota et al., 2009; Toyoda et al., 2021; Zhan et al., 2021). Fewer published N 2 O data exist in other North American Arctic Ocean regions, including the Northwest Passage and Baffin Bay (Kitidis et al., 2010; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As with CH4, the importance of the Arctic Ocean in the global N2O budget is currently poorly constrained, with some regions likely acting as N2O sinks and others as net sources (Fenwick et al, 2017;Yang et al, 2020;Zhan et al, 2021;Zhang et al, 2015). Thawing terrestrial permafrost may act as a net source of N2O to the atmosphere, but there is no consensus on whether thawing subsea permafrost will be a net source or sink of N2O (Voigt et al, 2017b;Voigt et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…nitrification and denitrification (Bange et al, 2010;Codispoti, 2010), and are likely to be impacted by ongoing Arctic change. Some studies have reported significant N2O supersaturation can occur in the Bering and Chukchi Seas (Hirota et al, 2009;Toyoda et al, 2021;Zhan et al, 2021). Fewer published N2O data exist in other North American Arctic Ocean regions, including the Northwest Passage, and Baffin Bay (Kitidis et al, 2010;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the North American AO it was suggested that high levels of N 2 O were largely associated with production in the shelf sediments of Chukchi and Bering Sea's with subsequent advection eastwards (Fenwick et al 2017). Supersaturations of N 2 O were also associated with the continental shelf for this region during the 7th Chinese National Arctic Research Expedition (Zhan et al 2017(Zhan et al , 2021 who also noted that offshore waters tended to be in equilibrium with the atmosphere. The Nordic Seas associated with the Greenland Basin and Fram Strait have been reported to be undersaturated in N 2 O (Rees et al 2021) and act as a permanent sink to atmospheric N 2 O (Zhan et al 2016).…”
Section: Current Understanding Of N 2 O and Ch 4 In Arctic Watersmentioning
confidence: 99%